Pemikiran Gus Dur Tentang Pendidikan Islam Multikultural - Mulyadi, Mulyadi (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aims to explore Gus Dur's views on multiculturalism and the concept of multicultural Islamic education. This research belongs to the category of library research, because the main data source comes from literature review. The collected data is then analyzed using content analysis techniques with a descriptive approach. Indonesia is a country that consists of various ethnic groups, races, ethnicities, religions, languages. This diversity is a uniqueness that characterizes the Indonesian nation, diversity is sunnatullah, but on one side of the diversity often lead to conflicts between groups that have differences from one another. Multiculturalism is an understanding that upholds the values ​​of tolerance between groups with differing views on ethnicity, religion, culture, race, ethnicity and gender, this understanding offers equality between groups, and further promotes human values, namely equal rights to life. One of the ways to provide multicultural understanding is through education. The results showed that Gus Dur's multiculturalism thinking included several aspects, namely, the indigenization of Islam who wanted to integrate Islam with local culture. Democracy and the enforcement of human rights is a logical consequence that is considered as one of the dimensions and an inseparable part of Islamic teachings, so that the commitment to uphold humanitarian values ​​is obligatory. Humanism and plurality are entirely based on a deep understanding of the teachings of Islam and NU's own scientific traditions. The characteristics of Gus Dur's multiculturalism thinking are highly anthropological theological that emphasizes social contextualism. And the results of Gus Dur's thoughts on the concept of Multicultural Islamic education include the idea of ​​Gus Dur in an effort to display the image of Islamic education into social life is a multicultural-based Islamic education. Gus Dur believes that multicultural Islamic education can be done with various approaches and strategies. The curriculum that must be achieved in multicultural-based Islamic education must contain the universalism of Islamic teachings, humanitarian principles, the purpose of education must be emphasized more on the affective and psychomotor aspects coupled with spiritual and humanism aspects. Application of multicultural Islamic education, so that students who study are students who have religious knowledge and have a strong general knowledge in a balanced way.